The principles of human computer interaction (HCI) in user interface design / Nor Anita Fairos Ismail, Sarina Sulaiman and Mohammad Ashari Alias - Ismail, Nor Anita Fairos; Sulaiman, Sarina; Alias, Mohammad Ashari (2006)
People interact with computers by means of a user interface or the "window" into the computer application. The system may have a myriad of functions. but if the user cannot find them. they cannot use them. A discipline that addresses humans using computers has evolved called Human-Computer Interaction (HCI), as well as basic principles of interface design and a user centered process to ensure that people can truly "use" the interface. Human-Computer Interaction (Hel) is the study of how to improve the design of user interfaces in order to support human activity. The goal of this paper is to present and discuss the HCI principles need to be concern in user interface design to making a usable system and product. Design means being good, not just looking good. A good interface makes it easy for users to tell the computer what they want to do. for the computer to request information from the users and for the computer to present understandable information. Clear communication between the user and the computer is the working premise of a well-designed interface. Therefore. the user interface is important to prospective viewers and may help gain attention and build confidence in using computer systems.